Adaptive Curriculum Integration in Islamic Primary Education: Bridging the Kurikulum Merdeka and Kurikulum Berbasis Cinta in an Indonesian Madrasah - Nurrohman, Febri Amin; Zakarya, Mohammad Aizzatu; Akyas, Gibran; Saputra, Axesa Haraja (HEUTAGOGIA: Journal of Islamic Education, 2026)
This study aims to analyze the adaptive curriculum model developed by MI Ma’arif Petet Ngargosari Samigaluh in integrating the Independent Curriculum (Kurikulum Merdeka) and the Love-Based Curriculum (Kurikulum Berbasis Cinta). Using a descriptive qualitative approach with a phenomenological design, data were collected through document analysis, classroom observation, and in-depth interviews with Islamic Education (PAI) teachers. The results reveal that the curriculum of MI Ma’arif Petet was designed to bridge national education policies with local community needs through three major components: intracurricular, cocurricular, and extracurricular programs. The values of love ḥubb Allāh (love for God), ḥubb al-waṭan wa al-bilād (love for the homeland), hubbunnaas (love for others), and ḥubb al-'ilm (love for knowledge) serve as the core foundation for character education. The implementation of the Love-Based Curriculum has transformed the PAI teachers’ teaching paradigm toward a more reflective and humanistic approach, enhancing students’ religiosity, empathy, and learning motivation. Despite challenges such as limited ICT facilities and insufficient training, teachers successfully overcame them through local innovations and collaborative practices. In conclusion, the adaptive curriculum model at MI Ma’arif Petet stands as a best practice for contextual Islamic education development that harmonizes national curriculum reforms with spiritual and humanistic values within the Merdeka Belajar framework. This study was limited to the madrasah ibtidaiyah level and involved only the perspectives of Islamic Education teachers and the principal; therefore, its findings cannot be broadly generalized to all Islamic educational contexts. Future research should include students, parents, and other madrasah stakeholders, as well as examine the long-term impact of the Love-Based Curriculum on students' character development, well-being, and academic achievement through longitudinal or comparative studies across diverse educational levels and Islamic school settings.